A kind of lanthanum carbonate hydroxide and preparation method thereof, lanthanum oxide and catalyst

By designing a unique morphology for basic lanthanum carbonate with three spindle-shaped plane parts and two curved surface parts, the problem of insufficient active sites is solved, catalytic activity and efficiency are improved, and structural stability is enhanced.

CN118619327BActive Publication Date: 2025-03-11WUHAN UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410899798.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-05
Publication Date
2025-03-11
Estimated Expiration
2044-07-05

AI Technical Summary

Technical Problem

The existing basic lanthanum carbonate has few active sites, which affects its application effect in the field of catalysts.

Method used

By designing the unique morphology of alkaline lanthanum carbonate, it includes three planar parts and two curved parts arranged in a spindle shape, so that its surface has more atomic steps, thereby increasing the active site.

Benefits of technology

The catalytic activity and catalytic efficiency of basic lanthanum carbonate in the catalyst is improved, while the stability of its structure is enhanced and the probability of structure collapse is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118619327B_ABST
    Figure CN118619327B_ABST
Patent Text Reader

Abstract

The present application relates to a lanthanum carbonate hydroxide and a preparation method thereof, lanthanum oxide and a catalyst. The present application relates to the field of inorganic chemical technology. The lanthanum carbonate hydroxide is provided with two curved portions arranged opposite to each other along its thickness direction, and the projection of the curved portions in the thickness direction is a triangle; the lanthanum carbonate hydroxide is provided with three shuttle-shaped planar portions on the periphery, and the two sides of the planar portions in the short axis direction are respectively connected to the two curved portions; the ends of the three planar portions in the long axis direction are connected in sequence, and the long axis of the planar portions constitutes the sideline of the triangle. The surface of lanthanum carbonate hydroxide has a large number of atomic steps. When applied to catalysts, it can increase active sites, thereby improving catalytic activity and catalytic efficiency. At the same time, the symmetrical structure formed by the three shuttle-shaped planar portions and the two curved portions makes the structure of lanthanum carbonate hydroxide more stable, reducing the probability of structural collapse.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of inorganic compounds, and in particular to a lanthanum basic carbonate and a preparation method thereof, lanthanum oxide and a catalyst. Background Art

[0002] Lanthanum basic carbonate not only has important applications in the fields of medicine and catalysts, but also shows potential research value in the field of materials science.

[0003] When lanthanum carbonate hydroxide is used in photocatalysts, its morphology has a direct impact on the catalytic effect of the photocatalyst. Existing lanthanum carbonate hydroxide is mostly rod-shaped, flake-shaped or spherical, and has few active sites, which affects its application. Summary of the invention

[0004] The present application provides a lanthanum carbonate hydroxide and a preparation method thereof, lanthanum oxide and a catalyst, so as to solve the problem in the related art that lanthanum carbonate hydroxide has few active sites, which affects its application.

[0005] In a first aspect, the present application provides a lanthanum carbonate hydroxide, wherein the lanthanum carbonate hydroxide is provided with two curved surface portions arranged opposite to each other along its thickness direction, and the projection of the curved surface portions in the thickness direction is a triangle;

[0006] The lanthanum carbonate hydroxide is provided with three shuttle-shaped planar portions on its circumference, and the two sides of the planar portions in the short axis direction are respectively connected to the two curved portions;

[0007] The ends of the three planar portions in the long axis direction are connected in sequence, and the long axes of the planar portions constitute the side lines of the triangle.

[0008] In the present application, the lanthanum carbonate hydroxide includes three shuttle-shaped planar portions and two curved portions, so that the surface of the lanthanum carbonate hydroxide has more atomic steps. When applied to a catalyst, the active sites of the lanthanum carbonate hydroxide can be increased, thereby improving the catalytic activity of the lanthanum carbonate hydroxide when applied to the catalyst and improving the catalytic efficiency. At the same time, the three shuttle-shaped planar portions and two curved portions form a three-dimensional symmetrical structure that makes the structure of the lanthanum carbonate hydroxide more stable and reduces the probability of structural collapse.

[0009] It should be noted that the thickness of the lanthanum basic carbonate may be 160 nm to 400 nm.

[0010] In some embodiments, the particle size of the lanthanum carbonate hydroxide is 400-1000 nm. Within this particle size range, the active sites of the lanthanum carbonate hydroxide can be further increased.

[0011] In some embodiments, the length of the major axis of the planar portion is d1, and the length of the minor axis of the planar portion is d2, wherein:

[0012] 400nm≤d1≤1000nm, the length of the major axis of the planar portion is within this range, which can increase the number of atomic steps on the edge between the planar portion and the curved portion, providing more active sites; and / or,

[0013] 160nm≤d2≤400nm. The length of the short axis of the planar portion is within this range, which can increase the number of atomic steps on the edge between the planar portion and the curved portion, thereby providing more active sites.

[0014] In a second aspect, the present application proposes a method for preparing lanthanum carbonate hydroxide, comprising the following steps:

[0015] Mixing a solution of a lanthanum salt with a surfactant to obtain a first mixed solution;

[0016] adding ammonium bicarbonate solution dropwise into the first mixed solution to obtain a second mixed solution;

[0017] The second mixed solution is heated in a hydrothermal reactor for reaction, centrifuged, and the filter residue is washed and dried to obtain lanthanum basic carbonate;

[0018] The lanthanum carbonate hydroxide is provided with two curved portions arranged opposite to each other along its thickness direction, and the projection of the curved portions in the thickness direction is a triangle;

[0019] The lanthanum carbonate hydroxide is provided with three shuttle-shaped planar portions on its circumference, and the two sides of the planar portions in the short axis direction are respectively connected to the two curved portions;

[0020] The ends of the three planar portions in the long axis direction are connected in sequence, and the long axes of the planar portions constitute the side lines of the triangle.

[0021] Since the lanthanum carbonate hydroxide includes three shuttle-shaped planar portions and two curved portions, the surface of the lanthanum carbonate hydroxide has more atomic steps. When applied to a catalyst, the active sites of the lanthanum carbonate hydroxide can be increased, thereby improving the catalytic activity of the lanthanum carbonate hydroxide when applied to the catalyst and improving the catalytic efficiency. At the same time, the symmetrical structure formed by the three shuttle-shaped planar portions and the two curved portions makes the structure of the lanthanum carbonate hydroxide more stable and reduces the probability of structural collapse.

[0022] The lanthanum salt can be dispersed by mixing the lanthanum salt solution with the surfactant, and the ammonium bicarbonate solution is dripped into the first mixed solution for mixing, so that the lanthanum ions are precipitated from the solution to form seed crystals. The weak alkalinity of ammonium bicarbonate can prevent the reaction from being too violent, which is conducive to controlling the reaction rate and making the seed crystals precipitate more uniformly. Then, under the action of the surfactant, the seed crystals grow anisotropically in the hydrothermal reactor to form lanthanum basic carbonate.

[0023] In some embodiments, the lanthanum salt includes at least one of lanthanum nitrate, lanthanum chloride and lanthanum sulfate. Using at least one of the above lanthanum salts can fully dissolve trivalent lanthanum ions in the reaction medium; and / or,

[0024] The surfactant includes polyethylene glycol, wherein the average molecular weight of the polyethylene glycol is 200 to 2000. The polyethylene glycol with an average molecular weight of 200 to 2000 can selectively protect specific crystal faces during the growth of lanthanum carbonate hydroxide crystals, so that the crystals grow anisotropically, thereby forming lanthanum carbonate hydroxide; and / or,

[0025] The particle size of the lanthanum carbonate hydroxide is 400 to 1000 nm. Compared with large-sized particles, the lanthanum carbonate hydroxide with nanostructure has a rich surface morphology and structure, which brings more superior performance. For example, lanthanum carbonate hydroxide nanomaterials can be used as catalysts for the oxidation reaction of compounds such as methanol. The surface of nano lanthanum carbonate hydroxide has more catalytic active sites, and the efficiency of the catalytic reaction will be significantly improved. Within this particle size range, the active sites of lanthanum carbonate hydroxide can be further increased; and / or,

[0026] The length of the major axis of the planar portion is d1, 400nm≤d1≤1000nm. When the length of the major axis of the planar portion is within this range, the number of atomic steps on the edge between the planar portion and the curved portion can be increased, thereby providing more active sites; and / or,

[0027] The length of the short axis of the planar portion is d2, 160nm≤d2≤400nm. The length of the short axis of the planar portion is within this range, which can increase the number of atomic steps on the edge between the planar portion and the curved portion, and provide more active sites.

[0028] In some embodiments, the solution of lanthanum salt is mixed with a surfactant to obtain a first mixed solution:

[0029] The mass ratio of the lanthanum salt to the surfactant is 1:(1-20). Within this range, the surfactant can fully wrap the crystal surface during the subsequent crystal growth process, protect specific crystal faces, and make the crystal grow anisotropically; and / or,

[0030] The mixing speed is 300 to 1200 rpm. Within this range, the lanthanum salt and the surfactant can be fully dispersed in water; and / or,

[0031] The mixing time is 1 hour to 3 hours. Within this mixing time range, the lanthanum salt and the surfactant can be fully dispersed in water.

[0032] In some embodiments, the ammonium bicarbonate solution is dripped into the first mixed solution to obtain a second mixed solution:

[0033] The dripping rate is 0.01 mL / s to 0.5 mL / s. Within this range, the lanthanum ions can be slowly precipitated in water to form uniform seed crystals and / or,

[0034] The molar ratio of the ammonium bicarbonate to the lanthanum ions in the lanthanum salt is greater than 2:1, and the molar ratio of the lanthanum salt to the ammonium bicarbonate is within this range, and the excess ammonium bicarbonate can fully precipitate the lanthanum ions; and / or,

[0035] The mixing temperature is 40-80° C. Within this mixing temperature range, the precipitation reaction of the lanthanum salt and ammonium bicarbonate can reach thermodynamic equilibrium as soon as possible, uniform precipitation seeds can be obtained, and the surfactant can be better dispersed in water; and / or,

[0036] The mixing time is 1 to 5 hours. Within this range, the evaporation of water can be reduced and the concentration of the reaction system can be maintained while ensuring sufficient reaction; and / or,

[0037] The mixing speed is 300-1200 rpm. Within this range, the precipitated crystal seeds and the surfactant can be more evenly dispersed in the water.

[0038] In some embodiments, the second mixed solution is heated in a hydrothermal reactor for reaction, centrifuged, and the filter residue is washed and dried to obtain lanthanum carbonate hydroxide:

[0039] The heating temperature is 110-220° C. Within this range, the pressure in the hydrothermal reactor can be higher than normal pressure, which is conducive to the anisotropic growth of lanthanum carbonate hydroxide crystals; and / or,

[0040] The heating time is 6 to 20 hours. Within this range, the crystal growth in the hydrothermal reaction can be carried out with sufficient time.

[0041] It should be noted that carrying out the reaction in a hydrothermal reactor is conducive to the anisotropic growth of the product crystals, and is more conducive to the formation of lanthanum basic carbonate under pressure conditions.

[0042] In a third aspect, the present application provides a lanthanum oxide, which is obtained by calcining the lanthanum basic carbonate prepared by the preparation method of the lanthanum basic carbonate of the first aspect or the lanthanum basic carbonate of the second aspect.

[0043] In a fourth aspect, the present application proposes a catalyst comprising the lanthanum oxide of the third aspect. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0045] Figure 1 This is a SEM image of the lanthanum carbonate hydroxide of Example 2 of the present application.

[0046] Figure 2 This is a SEM image of the lanthanum carbonate hydroxide of Example 2 of the present application.

[0047] Figure 3 This is a TEM image of lanthanum hydroxide carbonate of Example 2 of the present application.

[0048] Figure 4 This is the SEM image of the lanthanum carbonate hydroxide of Comparative Example 1 of the present application.

[0049] Figure 5 This is the SEM image of lanthanum hydroxide of Comparative Example 2 of the present application. DETAILED DESCRIPTION

[0050] In order to make the purpose, technical solution and advantages of the present application clearer, the technical solution of the present application will be clearly and completely described below in combination with the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present application.

[0051] Definition explanation:

[0052] Lanthanum Hydroxycarbonate

[0053] The chemical formula of lanthanum carbonate is La2(CO3)3(OH)4·xH2O, where La represents the lanthanum element, CO3 represents the carbonate ion, OH represents the hydroxyl group, and x represents the number of crystal water. This compound usually appears as white or yellow crystals, which are difficult to dissolve in water, but can be dissolved in acidic solutions.

[0054] Active site

[0055] Active sites are areas on the surface that can participate in chemical reactions. These active sites usually have high surface energy and unsaturated chemical bonds, which enable them to effectively interact with other molecules or ions.

[0056] Catalytic efficiency

[0057] Catalytic efficiency generally refers to the ability of a catalyst to increase the reaction rate in a chemical reaction, and catalytic efficiency is associated with the catalytic mechanism.

[0058] Specific content of the invention:

[0059] Lanthanum basic carbonate not only has important applications in the fields of medicine and catalysts, but also shows potential research value in the field of materials science.

[0060] When lanthanum carbonate hydroxide is used as a catalyst, its morphology has a direct impact on the catalytic effect of the photocatalyst. Existing lanthanum carbonate hydroxide is mostly rod-shaped, flake-shaped or spherical, and has few active sites, which affects its application.

[0061] In view of this, the embodiments of the present application provide a lanthanum carbonate hydroxide and a preparation method thereof, lanthanum oxide and a catalyst to solve the problem in the related art that lanthanum carbonate hydroxide has few active sites, which affects its application.

[0062] In the first aspect, the present application provides a lanthanum carbonate hydroxide, which is provided with two curved surface parts arranged opposite to each other along its thickness direction, and the projection of the curved surface parts in the thickness direction is a triangle; three shuttle-shaped planar parts are provided on the circumference of the lanthanum carbonate hydroxide, and the two side edges of the planar parts in the short axis direction are respectively connected to the two curved surface parts; the ends of the three planar parts in the long axis direction are connected in sequence, and the long axes of the planar parts constitute the side lines of the triangle.

[0063] The present application provides lanthanum carbonate hydroxide including three shuttle-shaped planar portions and two curved portions. When applied to a catalyst, the curved surfaces and corners of the lanthanum carbonate hydroxide expose more low-index crystal planes, and the resulting atomic steps and other regions are all catalytic active sites, thereby increasing the active sites of lanthanum carbonate hydroxide, thereby improving the catalytic activity of lanthanum carbonate hydroxide when applied to the catalyst and improving the catalytic efficiency. At the same time, the three shuttle-shaped planar portions and two curved portions form a three-dimensional symmetrical structure that makes the structure of lanthanum carbonate hydroxide more stable and reduces the probability of structural collapse.

[0064] It should be noted that the thickness of the lanthanum basic carbonate may be 160nm≤d2≤400nm.

[0065] In some embodiments provided in the present application, the particle size of the lanthanum carbonate hydroxide is 400 to 1000 nm. Compared with large-sized particles, the lanthanum carbonate hydroxide with nanostructure has a rich surface morphology and structure that brings more superior performance. For example, lanthanum carbonate hydroxide nanomaterials can be used as catalysts for the oxidation reaction of compounds such as methanol. The surface of nano lanthanum carbonate hydroxide has more catalytic active sites, and the efficiency of the catalytic reaction will be significantly improved. Within this particle size range, the active sites of lanthanum carbonate hydroxide can be further improved. The planar long axis d1 of the lanthanum carbonate hydroxide includes but is not limited to 400nm, 450nm, 500nm, 550nm, 600nm, 650nm, 700nm, 750nm, 800nm, 850nm, 900nm, 950nm or 1000nm, which can be measured by electron microscopy.

[0066] In some embodiments provided herein, the length of the major axis of the planar portion is d1, and the length of the minor axis of the planar portion is d2, wherein: 400nm≤d1≤1000nm, and the length of the major axis of the planar portion is within this range, providing more abundant active sites. The value of the length d1 of the major axis of the planar portion includes but is not limited to 400nm, 450nm, 500nm, 550nm, 600nm, 650nm, 700nm, 750nm, 800nm, 850nm, 900nm, 950nm or 1000nm.

[0067] In some embodiments provided herein, the length of the major axis of the planar portion is d1, and the length of the minor axis of the planar portion is d2, wherein: 160nm≤d2≤400nm, and the length of the minor axis of the planar portion is within this range, providing more abundant active sites. The value of the length d2 of the minor axis of the planar portion includes but is not limited to 160nm, 180nm, 200nm, 220nm, 240nm, 260nm, 280nm, 300nm, 320nm, 340nm, 360nm, 380nm, 400nm.

[0068] In a second aspect, the present application proposes a method for preparing lanthanum carbonate hydroxide, which is used to prepare the lanthanum carbonate hydroxide of the first aspect of the present application, comprising the following steps:

[0069] Mixing a solution of a lanthanum salt with a surfactant to obtain a first mixed solution;

[0070] adding ammonium bicarbonate solution dropwise into the first mixed solution to obtain a second mixed solution;

[0071] The second mixed solution is heated in a hydrothermal reactor for reaction, centrifuged, and the filter residue is washed and dried to obtain lanthanum basic carbonate.

[0072] The lanthanum carbonate hydroxide is provided with two curved portions arranged opposite to each other along its thickness direction, and the projection of the curved portions in the thickness direction is a triangle;

[0073] The lanthanum carbonate hydroxide is provided with three shuttle-shaped planar portions on its circumference, and the two sides of the planar portions in the short axis direction are respectively connected to the two curved portions;

[0074] The ends of the three planar portions in the long axis direction are connected in sequence, and the long axes of the planar portions constitute the side lines of the triangle.

[0075] Since the lanthanum carbonate hydroxide includes three shuttle-shaped planar portions and two curved portions, the surface of the lanthanum carbonate hydroxide has more atomic steps. When applied to a catalyst, the active sites of the lanthanum carbonate hydroxide can be increased, thereby improving the catalytic activity of the lanthanum carbonate hydroxide when applied to the catalyst and improving the catalytic efficiency. At the same time, the symmetrical structure formed by the three shuttle-shaped planar portions and the two curved portions makes the structure of the lanthanum carbonate hydroxide more stable and reduces the probability of structural collapse.

[0076] The lanthanum salt can be dispersed by mixing the lanthanum salt solution with the surfactant, and the ammonium bicarbonate solution is dripped into the first mixed solution for mixing, so that the lanthanum ions are precipitated from the solution to form seed crystals. The weak alkalinity of ammonium bicarbonate can prevent the reaction from being too violent, which is conducive to controlling the reaction rate and making the seed crystals precipitate more uniformly. Then, under the action of the surfactant, the seed crystals grow anisotropically in the hydrothermal reactor to form lanthanum basic carbonate.

[0077] In some embodiments provided in the present application, the lanthanum salt includes at least one of lanthanum nitrate, lanthanum chloride and lanthanum sulfate. By using at least one of the above lanthanum salts, trivalent lanthanum ions can be fully dissolved in the reaction medium.

[0078] In some embodiments provided herein, the surfactant includes polyethylene glycol, wherein the average molecular weight of the polyethylene glycol is 200 to 2000. Using polyethylene glycol with an average molecular weight of 200 to 2000, specific crystal faces can be selectively protected during the growth of lanthanum carbonate hydroxide crystals, so that the crystals grow anisotropically, thereby forming lanthanum carbonate hydroxide. The average molecular weight of the polyethylene glycol includes, but is not limited to, 200, 300, 400, 500, 600, 700, 800, 900, 1000, 1100, 1200, 1300, 1400, 1500, 1600, 1700, 1800, 1900 or 2000.

[0079] In some embodiments provided herein, the solution of the lanthanum salt is mixed with a surfactant to obtain a first mixed solution: the mass ratio of the lanthanum salt to the surfactant is 1: (1-20), and the mass ratio of the lanthanum salt to the surfactant is within this range, so that the surfactant can fully wrap the crystal surface during the subsequent crystal growth process, protect specific crystal faces, and make the crystal grow anisotropically. The mass ratio of the lanthanum salt to the surfactant includes but is not limited to 1: 1, 1: 3, 1: 5, 1: 8, 1: 10, 1: 12, 1: 15, 1: 18 or 1: 20.

[0080] In some embodiments provided in the present application, the particle size of the lanthanum carbonate hydroxide is 400 to 1000 nm. Compared with large-sized particles, the lanthanum carbonate hydroxide with nanostructure has a rich surface morphology and structure that brings more superior performance. For example, lanthanum carbonate hydroxide nanomaterials can be used as catalysts for the oxidation reaction of compounds such as methanol. The surface of nano lanthanum carbonate hydroxide has more catalytic active sites, and the efficiency of the catalytic reaction will be significantly improved. Within this particle size range, the active sites of lanthanum carbonate hydroxide can be further increased.

[0081] In some embodiments provided in the present application, the length of the long axis of the planar portion is d1, 400nm≤d1≤1000nm. The length of the long axis of the planar portion is within this range, which can increase the number of atomic steps on the edge between the planar portion and the curved portion, and provide more active sites.

[0082] In some embodiments provided in the present application, the length of the short axis of the planar portion is d2, 160nm≤d2≤400nm. The length of the short axis of the planar portion is within this range, which can increase the number of atomic steps on the edge between the planar portion and the curved portion, and provide more active sites.

[0083] In some embodiments provided herein, the solution of the lanthanum salt is mixed with the surfactant to obtain a first mixed solution: the mixing speed is 300 to 1200 rpm. Within this range, the lanthanum salt and the surfactant can be fully dispersed in water. The mixing speed includes but is not limited to 300 rpm, 400 rpm, 500 rpm, 600 rpm, 700 rpm, 800 rpm, 900 rpm, 1000 rpm, 1100 rpm, and 1200 rpm.

[0084] In some embodiments provided herein, the lanthanum salt solution is mixed with a surfactant to obtain a first mixed solution: the mixing time is 1 h to 3 h. Within this range, the lanthanum salt and the surfactant can be fully dispersed in water. The mixing time includes but is not limited to 1 h, 1.5 h, 2 h, 2.5 h, and 3 h.

[0085] In some embodiments provided herein, the ammonium bicarbonate solution is dripped into the first mixed solution to obtain a second mixed solution: the dripping rate is 0.01 mL / s to 0.5 mL / s, and the dripping rate is within this range, so that the lanthanum ions can be slowly precipitated in water to form uniform crystal seeds. The dripping rate includes but is not limited to 0.01 mL / s, 0.05 mL / s, 0.10 mL / s, 0.15 mL / s, 0.20 mL / s, 0.25 mL / s, 0.30 mL / s, 0.35 mL / s, 0.40 mL / s, 0.45 mL / s or 0.50 mL / s.

[0086] In some embodiments provided herein, the ammonium bicarbonate solution is dripped into the first mixed solution to obtain a second mixed solution: the molar ratio of the ammonium bicarbonate to the lanthanum ions in the lanthanum salt is greater than 2:1, and the molar ratio of the ammonium bicarbonate to the lanthanum ions in the lanthanum salt is within this range, and the excess ammonium bicarbonate can fully precipitate the lanthanum ions. The molar ratio of the ammonium bicarbonate to the lanthanum ions in the lanthanum salt includes but is not limited to 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1.

[0087] In some embodiments provided herein, the ammonium bicarbonate solution is dripped into the first mixed solution to obtain the second mixed solution: the mixing temperature is 40 to 80°C. Within this range, the precipitation reaction of the lanthanum salt and the ammonium bicarbonate can reach thermodynamic equilibrium as soon as possible, uniform precipitation seeds can be obtained, and the surfactant can be better dispersed in water. The mixing temperature includes but is not limited to 40°C, 50°C, 60°C, 70°C or 80°C.

[0088] In some embodiments provided herein, the ammonium bicarbonate solution is dripped into the first mixed solution to obtain the second mixed solution: the mixing time is 1 to 5 hours. Within this range, the evaporation of water can be reduced and the concentration of the reaction system can be maintained while ensuring sufficient reaction. The mixing time includes but is not limited to 1 hour, 1.5 hours, 2.0 hours, 2.5 hours, 3.0 hours, 3.5 hours, 4.0 hours, 4.5 hours or 5 hours.

[0089] In some embodiments provided herein, the ammonium bicarbonate solution is dripped into the first mixed solution and mixed to obtain the second mixed solution: the mixing speed is 300 to 1200 rpm. Within this range, the precipitated crystal seeds and the surfactant can be more evenly dispersed in the water. The mixing speed includes but is not limited to 300 rpm, 400 rpm, 500 rpm, 600 rpm, 700 rpm, 800 rpm, 900 rpm, 1000 rpm, 1100 rpm, and 1200 rpm.

[0090] In some embodiments provided in the present application, the second mixed solution is heated in a hydrothermal reactor for reaction, centrifuged, the filter residue is washed, and dried to obtain lanthanum carbonate hydroxide: the heating temperature is 110 to 220°C. The heating temperature within this range can make the pressure in the hydrothermal reactor higher than normal pressure, which is conducive to the anisotropic growth of lanthanum carbonate hydroxide crystals. The heating temperature includes but is not limited to 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, 210°C or 220°C.

[0091] In some embodiments provided herein, the second mixed solution is heated in a hydrothermal reactor, centrifuged, the filter residue is washed, and dried to obtain lanthanum carbonate hydroxide: the heating time is 6 to 20 hours, and the heating time within this range can allow sufficient time for crystal growth in the hydrothermal reaction. The heating time includes but is not limited to 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, 13 hours, 14 hours, 15 hours, 16 hours, 17 hours, 18 hours, 19 hours or 20 hours.

[0092] In a third aspect, the present application provides a lanthanum oxide, which is obtained by calcining the lanthanum carbonate hydroxide prepared by the lanthanum carbonate hydroxide method of the first aspect or the lanthanum carbonate hydroxide prepared by the preparation method of the lanthanum carbonate hydroxide of the second aspect. The process of preparing lanthanum oxide from lanthanum carbonate hydroxide usually includes a heat treatment step, that is, converting lanthanum carbonate hydroxide into lanthanum oxide by thermal decomposition. The thermal decomposition temperature of lanthanum carbonate hydroxide is usually above 500°C, so the calcination temperature above 500°C can achieve the decomposition of lanthanum carbonate hydroxide into lanthanum oxide.

[0093] In a fourth aspect, the present application proposes a catalyst, including the lanthanum oxide of the third aspect. For example, as an automobile exhaust purification catalyst, it helps reduce the emission of harmful gases, such as carbon monoxide and nitrogen oxides. Or in chemical synthesis catalysis, after being doped with other substances, lanthanum oxide can catalyze the oxidation reaction of carbon monoxide and the reaction of carbon monoxide hydrogenation to produce methane. In addition, it can also be used as an effective selective catalyst for the oxidative coupling of methane to produce ethane and ethylene.

[0094] The technical solution provided in this application is described in detail below with reference to the embodiments and drawings.

[0095] Example 1

[0096] Embodiment 1 of the present application provides a lanthanum carbonate hydroxide, wherein the lanthanum carbonate hydroxide is provided with two curved surface portions arranged opposite to each other along its thickness direction, and the projection of the curved surface portions in the thickness direction is a triangle; three shuttle-shaped planar portions are provided on the circumference of the lanthanum carbonate hydroxide, and the two side edges of the planar portions in the short axis direction are respectively connected to the two curved surface portions; the ends of the three planar portions in the long axis direction are connected in sequence, and the long axes of the planar portions constitute the side lines of the triangle.

[0097] The particle size of the lanthanum basic carbonate is 1000 nm;

[0098] The length of the major axis of the planar portion was 1000 nm, and the length of the minor axis of the planar portion was 400 nm.

[0099] Example 1 of the present application also provides a method for preparing lanthanum carbonate hydroxide, comprising the following steps:

[0100] 1.7 g of lanthanum nitrate solution was mixed with 1.5 mL of polyethylene glycol with an average molecular weight of 400, and the mixture was stirred at 300 rpm at 40° C. for 1 h to obtain a first mixed solution;

[0101] 20 mL of 0.5 mol / L ammonium bicarbonate solution was dripped into the first mixed solution at a rate of 0.01 mL / s, and mixed at 40° C. and 500 rpm for 1 h to obtain a second mixed solution;

[0102] The second mixed solution was heated at 110° C. for 6 h in a hydrothermal reactor, centrifuged, the filter residue was washed, and dried at 60° C. to obtain lanthanum basic carbonate.

[0103] Example 2

[0104] Embodiment 2 of the present application provides a lanthanum carbonate hydroxide, which is provided with two curved surface portions arranged opposite to each other along its thickness direction, and the projection of the curved surface portions in the thickness direction is a triangle; three shuttle-shaped planar portions are provided on the circumference of the lanthanum carbonate hydroxide, and the two side edges of the planar portions in the short axis direction are respectively connected to the two curved surface portions; the ends of the three planar portions in the long axis direction are connected in sequence, and the long axes of the planar portions constitute the side lines of the triangle.

[0105] The particle size of the lanthanum basic carbonate is 800 nm;

[0106] The length of the major axis of the planar portion was 800 nm, and the length of the minor axis of the planar portion was 320 nm.

[0107] Example 2 of the present application also provides a method for preparing lanthanum carbonate hydroxide, comprising the following steps:

[0108] 1.7 g of lanthanum nitrate solution was mixed with 6 mL of polyethylene glycol having an average molecular weight of 400, and the mixture was stirred at 500 rpm at 40° C. for 2 h to obtain a first mixed solution;

[0109] Add 20 mL of 0.5 mol / L ammonium bicarbonate solution to the first mixed solution at a rate of 0.2 mL / s, and mix at 60° C. and 500 rpm for 3 h to obtain a second mixed solution;

[0110] The second mixed solution was heated at 150° C. for 12 h in a hydrothermal reactor, centrifuged, the filter residue was washed, and dried at 60° C. to obtain lanthanum basic carbonate.

[0111] Example 3

[0112] Example 3 of the present application provides a lanthanum carbonate hydroxide, which is provided with two curved surface parts arranged opposite to each other along its thickness direction, and the projection of the curved surface parts in the thickness direction is a triangle; three shuttle-shaped planar parts are provided on the circumference of the lanthanum carbonate hydroxide, and the two side edges of the planar parts in the short axis direction are respectively connected to the two curved surface parts; the ends of the three planar parts in the long axis direction are connected in sequence, and the long axes of the planar parts constitute the side lines of the triangle.

[0113] The particle size of the lanthanum basic carbonate is 400 nm;

[0114] The length of the major axis of the planar portion was 400 nm, and the length of the minor axis of the planar portion was 160 nm.

[0115] Example 3 of the present application also provides a method for preparing lanthanum carbonate hydroxide, comprising the following steps:

[0116] 1.7 g of lanthanum nitrate solution was mixed with 30 mL of polyethylene glycol having an average molecular weight of 400, and the mixture was stirred at 1200 rpm at 40° C. for 3 h to obtain a first mixed solution;

[0117] Add 20 mL of 0.5 mol / L ammonium bicarbonate solution dropwise into the first mixed solution at a rate of 0.5 mL / s, and mix at 80° C. and a stirring speed of 1200 rpm for 5 h to obtain a second mixed solution;

[0118] The second mixed solution was heated at 220° C. for 20 h in a hydrothermal reactor, centrifuged, the filter residue was washed, and dried at 60° C. to obtain lanthanum basic carbonate.

[0119] Comparative Example 1

[0120] Comparative Example 1 of the present application provides a method for preparing lanthanum basic carbonate, which is similar to Example 1, except that the preparation method of Comparative Example 1 does not react in a hydrothermal reactor.

[0121] Comparative Example 2

[0122] Comparative Example 2 of the present application provides a method for preparing lanthanum hydroxide carbonate, which is similar to Example 1, except that the ammonium bicarbonate solution is replaced with concentrated ammonia water in the preparation method of Comparative Example 2. The results show that the use of concentrated ammonia water cannot fully precipitate lanthanum, and only a small amount of lanthanum hydroxide nanorods can be obtained, and the catalyst yield is extremely low.

[0123] Performance Testing

[0124] The lanthanum basic carbonate prepared in Examples 1 to 3 and Comparative Examples 1-2 was calcined to form lanthanum oxide, which was used as a catalyst for the oxidative coupling reaction of methane to evaluate its catalytic ability (yield of C2 hydrocarbons such as ethylene and ethane). The specific catalytic ability evaluation steps are as follows:

[0125] 0.2 g of 40-mesh catalyst and 0.8 g of quartz sand were mixed and loaded into a quartz reaction tube with a diameter of 10 mm. A mixed reaction gas of 75% methane and 25% oxygen was introduced at a flow rate of 240 mL / min. The reaction products were monitored online by gas chromatography at a feed temperature of 550°C and the yield of C2 hydrocarbons was calculated.

[0126] The results are shown in Table 1.

[0127] Table 1 Catalytic performance of lanthanum carbonate hydroxide in Examples 1 to 3 and Comparative Examples 1 to 2

[0128] C2 hydrocarbon yield Example 1 15.7% Example 2 16.5% Example 3 17.1% Comparative Example 1 13.0% Comparative Example 2 Catalyst yield is too low to be used for catalytic evaluation

[0129] Since the reaction in Comparative Example 1 was not carried out in a hydrothermal reactor, the product was in the form of flakes, and there were fewer active sites such as low-coordinated atomic steps, so the catalytic performance was average.

[0130] Since concentrated ammonia water is used as the precipitant in Comparative Example 2, lanthanum ions cannot be fully precipitated, and the catalyst yield is extremely low. From the perspective of atom economy, this method is not suitable for the synthesis of methane oxidative coupling catalysts.

[0131] Figure 1 is the SEM image of the lanthanum carbonate hydroxide of Example 2, Figure 2 is the SEM image of the lanthanum basic carbonate of Example 2, Figure 1 and Figure 2 It can be seen that the lanthanum carbonate hydroxide is provided with two curved surface portions arranged opposite to each other along its thickness direction, and the projection of the curved surface portions in the thickness direction is a triangle; three shuttle-shaped planar portions are provided on the circumference of the lanthanum carbonate hydroxide, and the two sides of the planar portions in the short axis direction are respectively connected to the two curved surface portions; the ends of the three planar portions in the long axis direction are connected in sequence, and the long axis of the planar portion constitutes the side line of the triangle. Figure 2 (left) and Figure 2 (Right) The view perpendicular to the triangular face and the view perpendicular to the plane, respectively.

[0132] Figure 3 TEM image of lanthanum carbonate hydroxide of Example 2, Figure 3 It can be seen that the projection of the curved portion in the thickness direction is a triangle, and the plane portion is arranged in a shuttle shape. Figure 3 (left) and Figure 3 (Right) The view perpendicular to the triangular face and the view perpendicular to the plane, respectively.

[0133] Figure 4 This is the SEM image of the lanthanum carbonate hydroxide of Comparative Example 1. Figure 4 It can be seen that the lanthanum basic carbonate of Comparative Example 1 is in the form of flakes.

[0134] Figure 5 The SEM image of the lanthanum hydroxide of Comparative Example 2 is shown in FIG. Figure 5 The product was found to be in the form of rods with a length of 100 to 300 nm.

[0135] In summary, by virtue of the lanthanum carbonate hydroxide including three shuttle-shaped planar portions and two curved portions, when applied to a catalyst, the active sites of the lanthanum carbonate hydroxide can be increased, thereby improving the catalytic activity of the lanthanum carbonate hydroxide when applied to the catalyst and improving the catalytic efficiency. At the same time, the symmetrical structure formed by the three shuttle-shaped planar portions and the two curved portions makes the structure of the lanthanum carbonate hydroxide more stable, reducing the probability of structural collapse.

[0136] In the description of this specification, the description with reference to the terms "one embodiment / method", "some embodiments / methods", "example", "specific example" or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment / method or example are included in at least one embodiment / method or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment / method or example. Moreover, the specific features, structures, materials or characteristics described may be combined in a suitable manner in any one or more embodiments / methods or examples. In addition, those skilled in the art may combine and combine the different embodiments / methods or examples described in this specification and the features of the different embodiments / methods or examples, unless they are contradictory.

[0137] It should be noted that, in the present application, relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply that there is any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that the process, method, article or equipment including a series of elements includes not only those elements, but also includes other elements not explicitly listed, or also includes elements inherent to such process, method, article or equipment. In the absence of more restrictions, the elements defined by the sentence "comprise one..." do not exclude the existence of other identical elements in the process, method, article or equipment including the elements. In the present application, the meaning of "multiple" is at least two, such as two, three, etc., unless otherwise clearly and specifically stipulated.

[0138] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.

Claims

1. A lanthanum carbonate hydroxide, characterized in that The lanthanum carbonate hydroxide is provided with two curved surface portions which are arranged opposite to each other along the thickness direction thereof, and the projection of the curved surface portions in the thickness direction is a triangle; The lanthanum carbonate hydroxide is provided with three shuttle-shaped planar portions on its circumference, and the two sides of the planar portions in the short axis direction are respectively connected to the two curved portions; The ends of the three planar portions in the long axis direction are connected in sequence, and the long axes of the planar portions constitute the side lines of the triangle; The particle size of the lanthanum basic carbonate is 400 nm; The length of the major axis of the planar portion is 400 nm, and the length of the minor axis of the planar portion is 160 nm; The preparation method of the lanthanum carbonate hydroxide comprises the following steps: 1.7 g of lanthanum nitrate solution was mixed with 30 mL of polyethylene glycol having an average molecular weight of 400, and the mixture was stirred at 1200 rpm at 40° C. for 3 h to obtain a first mixed solution; Add 20 mL of 0.5 mol / L ammonium bicarbonate solution dropwise into the first mixed solution at a rate of 0.5 mL / s, and mix at 80° C. and a stirring speed of 1200 rpm for 5 h to obtain a second mixed solution; The second mixed solution is heated at 220° C. for 20 h in a hydrothermal reactor, centrifuged, the filter residue is washed, and dried at 60° C. to obtain the lanthanum basic carbonate.

2. A lanthanum oxide, characterized in that It is prepared by calcining the lanthanum basic carbonate as claimed in claim 1.

3. A catalyst, characterized in that Comprising the lanthanum oxide as described in claim 2.

Citation Information

Patent Citations

  • Application of lanthanum compound as photo-catalyst and preparation method of lanthanum compound

    CN103933962A